Positioning model: systematization of experiences, TEC case (National Administration Journal, 2025)
Through strategic marketing, positioning, segmentation, and value strategies are developed to enable differentiation in competitive environments, allowing products and services to occupy a place in the consumer’s mind.This presentation introduces a systematization of experiences based on the positioning model developed for the Costa Rica Institute of Technology, applied to the promotion and sale of services offered by its research centers.As a result of having a strategic marketing framework, the research centers mentioned improved their market recognition and increased their sales within a niche market characteristic of the services they provide.
Keywords: Positioning; brand; reputation; strategies; value proposition